The Influence of Leadership Style and Work Discipline on Employee Work Performance at PDAM Tirta Griya - Abdul Azis; Ade Solahudin; Sandi Nasrudin Wibowo (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2023)
The purpose of this study is to determine the authority of work discipline and leadership style on employee performance. The research was conducted at PDAM Tirta Griya Nata Cirebon with a total sample of 66 respondents. The determination of respondents selected through the technique of Probability Sampling with the type of sample is Random Sampling. Sampling from some populations without any difference is called probability sampling. The data analysis method used validity, reliability, classical assumptions, regression analysis, as well as t-test and F- a test which was processed through the IBM SPSS 23 (Special Package for Statistical Science) application. The results showed that the work discipline and sustainable leadership style on employee performance. The variable of work discipline and leadership style on employee performance has a significant positive effect of 27.5% and the remaining 72.5% is influenced by other factors. For PDAM Tirta Griya Nata Cirebon, it is important to pay attention to the leadership style given to employees and improve employee work discipline in order to create high employee performance and have a good impact on PDAM Tirta Griya Nata Cirebon.